The best CCT for appreciation of paintings under daylight illuminants is different for occidental and oriental viewers - Nascimento, Sérgio M. C. (2021)
The illumination critically influences the visual appreciation of paintings. Several studies suggest that daylight with a correlated color temperature (CCT) around 5,000 K is optimal for visual appreciation of paintings by occidental viewers. It is unclear, however, how much cultural or geographic factors influence optimal lighting. The aim of this work was to investigate whether preferred lighting is influenced by cultural or geographic factors by comparing occidental and oriental viewers' preferences in exact the same experimental conditions. The stimuli for the experiment were colorimetrically calibrated images of the paintings synthetized from hyperspectral imaging data. Of the 42 paintings tested, abstract and figurative, 32 were from occidental painters and 10 from oriental painters. In the experiment, observers could change the CCT of daylight illumination in the range 3,600 K-25,000 K and their task was to select the one producing the best subjective visual impression for each painting. Stimuli were displayed on calibrated CRT monitors, 19 Japanese observers carried out the experiment in Japan and 16 Portuguese observers carried out the experiment in Portugal. Consistently with published data, Portuguese observers preferred, on average, daylight with a CCT a little above 5,000 K. Crucially, Japanese observers systematically required a significantly higher CCT. The data suggests that cultural or geographic factors critically influence optimal lighting for paintings.